Integrating media content analysis, reception analysis, and media effects studies - Schmälzle, Ralf; Huskey, Richard (Frontiers in Neuroscience, 2023)
Every day, the world of media is at our fingertips, whether it is watching movies, listening to the radio, or browsing online media. On average, people spend over 8 h per day consuming messages from the mass media, amounting to a total lifetime dose of more than 20 years in which conceptual content stimulates our brains. Effects from this flood of information range from short-term attention bursts (e.g., by breaking news features or viral ‘memes’) to life-long memories (e.g., of one’s favorite childhood movie), and from micro-level impacts on an individual’s memory, attitudes, and behaviors to macro-level effects on nations or generations. The modern study of media’s influence on society dates back to the 1940s. This body of mass communication scholarship has largely asked, “what is media’s effect on the individual?” Around the time of the cognitive revolution, media psychologists began to ask, “what cognitive processes are involved in media processing?” More recently, neuroimaging researchers started using real-life media as stimuli to examine perception and cognition under more natural conditions. Such research asks: “what can media tell us about brain function?” With some exceptions, these bodies of scholarship often talk past each other. An integration offers new insights into the neurocognitive mechanisms through which media affect single individuals and entire audiences. However, this endeavor faces the same challenges as all interdisciplinary approaches: Researchers with different backgrounds have different levels of expertise, goals, and foci. For instance, neuroimaging researchers label media stimuli as “naturalistic” although they are in many ways rather artificial. Similarly, media experts are typically unfamiliar with the brain. Neither media creators nor neuroscientifically oriented researchers approach media effects from a social scientific perspective, which is the domain of yet another species. In this article, we provide an overview of approaches and traditions to studying media, and we review the emerging literature that aims to connect these streams. We introduce an organizing scheme that connects the causal paths from media content → brain responses → media effects and discuss network control theory as a promising framework to integrate media content, reception, and effects analyses.